QUALITY ASSESSMENT OF SILKWORM SEED LOT AT SILKWORM BREEDING ENTERPRISES - M.J.Abdurasulova (Web of Journals Publishing, 2025)
The transition of our country's economy to market relations demands an improvement in the quality of agricultural products and elevating them to a level where they can compete in the global market. In this regard, an important task for the workers of the sericulture sector is to prepare high-quality silkworms that meet world standards. To achieve this, it is necessary to strictly follow the sericulture agrotechnics to obtain silkworms with clean cocoons that are well-formed, long, slender, and free from defects. Unfortunately, it is known that a significant number of defective silkworms are present even in purebred silkworm groups and are delivered to silkworm reception points.
Keywords: Silkworm, defective silkworms, slender fiber, mulberry silkworm, diseases, purebred silkworms, sericulture factory.